2019
DOI: 10.1038/s41598-019-43753-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of coffee floral traits under two different agricultural practices

Abstract: Floral traits and rewards are important in mediating interactions between plants and pollinators. Agricultural management practices can affect abiotic factors known to influence floral traits; however, our understanding of the links between agricultural practices and floral trait expression is still poorly understood. Variation in floral morphological, nectar, and pollen traits of two important agricultural species, Coffea arabica and C. canephora , was assessed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 77 publications
3
17
0
Order By: Relevance
“…They also observed a decrease in fresh flower weight and an increase in flower diameter, indicating a change in resource allocation as a result of shading 51 . When examining shaded and unshaded coffee plantations, Prado et al 52 also observed differences in flower morphology, but did not see a difference in nectar or pollen levels, which are key drivers of pollinating insect populations 52 . The increased floral abundance and delayed bloom timing that we observed in the partial shade (versus full sun) could be the result of reduced sun hours on photoperiodicity 48 , 49 , photosynthetic efficiency 51 , or transpiration efficiency 53 ; the decrease in soil temperature and moisture on germination 49 , root establishment 9 ; or a combination of these strategies and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed a decrease in fresh flower weight and an increase in flower diameter, indicating a change in resource allocation as a result of shading 51 . When examining shaded and unshaded coffee plantations, Prado et al 52 also observed differences in flower morphology, but did not see a difference in nectar or pollen levels, which are key drivers of pollinating insect populations 52 . The increased floral abundance and delayed bloom timing that we observed in the partial shade (versus full sun) could be the result of reduced sun hours on photoperiodicity 48 , 49 , photosynthetic efficiency 51 , or transpiration efficiency 53 ; the decrease in soil temperature and moisture on germination 49 , root establishment 9 ; or a combination of these strategies and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Angiosperms have evolved strategies to alter bloom time, length and intensity in response to environmental conditions (light, temperature, moisture) 9 , 48 52 . The effects of shading on flowering depend on the individual species preferences and local growing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies selected for Indonesia (n = 2) does not reflect the importance of this country in terms of world coffee production (Food and Agriculture Organization of the United Nations 2020). Both studies in USA were from Puerto Rico (Prado et al 2018(Prado et al , 2019. According to Köppen's classification (Beck et al 2018), the climates encountered in the studies were (1) Tropical-Rainforest (Af, n = 6), (2) Tropical-Monsoon (Am, n = 7) and (3) Tropical-Savannah (Aw, n = 17).…”
Section: Global Distribution Of Shade Tree and Robusta Studiesmentioning
confidence: 99%
“…In 3 out of 30 experiments, the effect of overstory trees on coffee physicochemical, physiological and photosynthetic parameters interacted with robusta clones and in some cases there were comparisons with the arabica species (Anim- 1 For C153, LB1, GG and JM2 clones, mean of % of shade with the highest plant height, collar diameter, length of main branch, crown diameter and number of plagiotropic branches is depicted 2 For 03V, 06V and 12V clones, mean of % of shade with the highest mean orthotropic and plagiotropic branch growth rate and plagiotropic branch node emission rate is depicted 3 For C153, LB1, GG and JM2 clones, % of shade with the highest number of fruits is depicted Prado et al 2019;Rodriguez-Lopez et al 2013). For robusta clone 03, leaf chlorophyll and carotenoid concentrations increased with morning shade, yet there was no effect on clone 120.…”
Section: Effects Of Shade Trees On Robusta Physicochemical Physiologimentioning
confidence: 99%
“…Coffee shade trees also play an essential role in the life quality of insect pollinators. The total nitrogen content in coffee flower pollens protected by the shade is higher than that in coffee pollens that are exposed to light intensities [16]. The Nitrogen content in pollen may increase the life quality of insect pollinators for the sufficiency of their feed nutrition.…”
Section: Introductionmentioning
confidence: 92%